Is there Regional Tax Competition in Belgium? - Hylke Vandenbussche; Boudewijn Janssen; Karen Crabbé (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2004)
In this paper we study the detfirminants of Effective Corporate Tax Rates (ETR) of large Belgian firms. Our empirical model to explain firm level heterogeneity in ETRs, includes firm characteristics, sector membership, variables capturing legal tax breaks and location variables. Our results can be summarized as follows. First, we find the average Effective Tax Rate to be around 26% in the period 1993-2002, whereas the country wide Statutory Tax Rate (STR) in that period was 40.17 %. Second, we find that highly leveraged firms and R&D intensive firms have substantially lower Effective tax rates. Third, we observe substantial sector level heterogeneity in corporate tax burdens. Fourth, our findings are indicative of regional tax differences with a lower average ETR in Wallonia. And finally, we observe that firm level Effective Tax Rates have increased in recent years.
Keywords: 330; Effective Tax Rates; Company accounts; Belgian firms; Steuerwettbewerb; Unternehmensbesteuerung; Regionale Disparität; Belgien